Contract Agriculture Lessons from Experiences in Costa Rica - Chiriboga, Manuel; Charnay, Romain; Chehab, Carol (Washington, DC: World Bank, 2012)
Contract farming or contract agriculture is a practice by which agro-industrial processors, exporters, domestic suppliers to supermarkets and other interested actors contract primary production with producers. The factors that have encouraged contract farming in Costa Rica can be grouped in three major areas: 1) interest of the contractors to guarantee supply of the products under specific quality standards required by mass distribution systems or by importers; 2) avoiding problems related to administration of farms and particularly managing of personnel; and 3) distribution of risks that could be derived by high concentration of production. The study concludes are that there is a high variety in the modalities of contract farming; arrangements vary depending on crops or animal products; most contract agreements include clauses on technical assistance, quality controls and pricing, and few include financing; support and guarantee of purchase of the products helps farmers in their arrangements to obtain financing; the degree of formality of contracts is varied, being more stringent when contractors are private firms; and there is no special legislation for the specific case of contract farming. The benefits of contract farming accrue to producers and contractors, yet the former share a less significant portion of the benefits if one considers that they share most of the remaining risks.